2021
DOI: 10.1038/s41598-021-99784-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Indian diabetes prevention programme on association of adipokines and a hepatokine with incident diabetes

Abstract: To study the association and possible predictive role of visfatin, resistin, fetuin-A and chemerin with incident type 2 diabetes (T2DM) among Asian Indians with prediabetes. Their association with insulin resistance, β-cell function, glycaemia and anthropometry were also studied. This is a nested case–control study of a large 2-year prospective prevention trial in persons at high risk of developing T2DM. Baseline HbA1c values between 6.0% (42 mmol/mol) and 6.2% (44 mmol/mol) were chosen for this analysis (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a prior study, Ruan et al [ 11 ] showed that endolipin is an independent risk factor for the occurrence of stroke in hypertensive patients. Susairaj et al [ 12 ] showed that serum endostatin predicted type 2 diabetes mellitus with an AUC of 0.77 and a sensitivity and specificity of 75%. Kumar et al [ 13 ] stated that Gal-3 expression is closely related to the risk of microvascular complications in patients with type 2 diabetes mellitus, and could be used as a valid factor in the diagnosis and evaluation of microvascular and macrovascular complications in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, Ruan et al [ 11 ] showed that endolipin is an independent risk factor for the occurrence of stroke in hypertensive patients. Susairaj et al [ 12 ] showed that serum endostatin predicted type 2 diabetes mellitus with an AUC of 0.77 and a sensitivity and specificity of 75%. Kumar et al [ 13 ] stated that Gal-3 expression is closely related to the risk of microvascular complications in patients with type 2 diabetes mellitus, and could be used as a valid factor in the diagnosis and evaluation of microvascular and macrovascular complications in patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-A was also associated with diabetic risk factors. Baseline levels of Fetuin-A independently contributed to the progression of prediabetes to T2D (54). Fetuin-A is capable of crossing the blood-brain barrier and is associated with depression regardless of insulin sensitivity status (55).…”
Section: Fetuin-a Animal Studies Clinical Studiesmentioning
confidence: 97%